Following up internet‐delivered cognitive behaviour therapy (CBT): A longitudinal qualitative investigation of clients' usage of CBT skills. (13th June 2021) - Eilert, Nora; Timulak, Ladislav; Duffy, Daniel; Earley, Caroline; Enrique, Angel; Kennedy, Polly; McCormack, Clare; Palacios, Jorge; Wogan, Rebecca; Richards, Derek
Abstract: Background: While the acquisition and application of Cognitive Behaviour Therapy (CBT) skills is a core component and likely mechanism of effect maintenance in all CBT‐based treatments, the extent of post‐therapeutic CBT skills usage among internet‐delivered CBT (iCBT) clients remains under‐researched. Method: Nested within a pragmatic randomized controlled trial, 241 participants received an 8‐week supported iCBT intervention for anxiety and/or depression and answered open‐ended questions about their use and experience of CBT skills at 3‐, 6‐, 9‐, and 12‐month follow‐up. Recurrent, cross‐sectional qualitative analysis following the descriptive and interpretive approach was used to create a taxonomy, through which all qualitative data was coded. Results: In total, 479 qualitative responses across 181 participants were analysed. Participants reported using a wide range of CBT skills and associated helpful and hindering experiences and impacts. The reasons for discontinued CBT skills usage were diverse, ranging from rare adverse effects to healthy adaptation. Conclusion: The study shows how clients receiving iCBT in routine care learn CBT skills during treatment and utilize them in productive ways post‐treatment. Findings coincide with similar research in face‐to‐face CBT and may inform future research to drive innovation and iCBT intervention development.